Comparison of lidocaine bicarbonate with fentanyl and chloroprocaine for epidural anesthesia during cesarean section: a randomized, controlled, double-blind clinical trial - Yu, Jing; Liu, Jingjing; Wang, Chenran; Song, Congzhong; He, Gangming; Liu, Chaohui; Mei, Zhong; Huang, Shaoqiang (Frontiers in Pharmacology, 2024)
Chloroprocaine and lidocaine bicarbonate are commonly used for epidural anesthesia because of their rapid onset, particularly in the case of conversion from epidural labor analgesia to emergency cesarean section. However, it is unclear whether lidocaine bicarbonate combined with fentanyl has an advantage over chloroprocaine alone in emergency cesarean section. In this study, 102 women who underwent elective cesarean section received 15 ml 3% chloroprocaine and 1 ml saline (CP group) or 15 ml 1.73% lidocaine bicarbonate and 1 ml fentanyl 50 μg (LF group) for epidural anesthesia. Nociceptive block level was assessed by pinprick and recorded every minute. The primary outcome was the onset time to T6 block. The median onset time to T6 analgesia was 10 [10, 10] min in the CP group and 10 [7, 10] min in the LF group (COX model for CP versus LF, HR 0.47, 95% CI 0.23-0.95, P=0.035). The median onset time to T8 analgesia was 7 [5, 9] min in CP group and 5 [4, 7] min in LF group (COX model for CP versus LF, HR 0.61, 95% CI 0.39-0.95, P=0.027). The proportion of hypotension episodes occurring before delivery in LF group was lower than that in CP group (P=0.011). The incidence of block level ≥ T4 after supplemental dosing in the LF group was lower than that in the CP group (P=0.031). Compared with 3% chloroprocaine, 1.73% lidocaine bicarbonate combined with fentanyl 50 μg has a slightly faster onset time and less hypotension in epidural anesthesia for cesarean section.